Contextualizing Living Hadith through al-Bu'dain al-Zamāni wa al-Makāni: Evidence from Pesantren Ar-Raudlatul Hasanah Medan - Ahmad Faisal; Rasyidin; Abdul Aziz Sebayang; Ilias, Mohd Faeez (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
Contemporary hadith studies increasingly examine how prophetic traditions are practiced within Muslim communities, however most remain descriptive and lack a methodological framework linking the original context of hadith with its contemporary manifestations. This study addresses that gap by examining al-Bu’dain al-Zamāni wa al-Makāni (the dimensions of time and place) as an analytical framework for understanding Living Hadith at Ar-Raudlatul Hasanah Pesantren in Medan. It investigates how this approach can map and critically assess the implementation of hadith values in the pesantren tradition, particularly in muhadharah, hadith learning, and congregational dhikr. Using qualitative field research, data were collected through participant observation, in-depth interviews with twelve informants (pesantren leaders, teachers, and students), and documentation of religious activities, then analyzed using qualitative content analysis based on al-Bu’dain al-Zamāni wa al-Makāni. The findings indicate that these practices constitute an actualization of prophetic teachings contextualized by the educational and cultural needs of the pesantren. The framework distinguishes universal religious principles (ṡawābit) from context-dependent applications (mutaghayyirāt), while providing a methodological basis for evaluating their relevance through maqāṣid al-sharī’ah. The study concludes that al-Bu’dain al-Zamāni wa al-Makāni contributes significantly to Living Hadith studies by bridging textual tradition, pesantren practice, and contemporary social reality, and by offering a critical instrument that moves beyond description toward normative evaluation of religious practice.